2010
DOI: 10.1111/j.1540-8175.2009.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Annular Velocities Generated by Speckle Tracking Imaging: Reproducibility and Correlation with Tissue Doppler Velocities

Abstract: E' by VVI is lower than by TDI with a poor agreement between the measurements, which are therefore not interchangeable. Although VVI can be performed offline, this method is dependent on image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…27 The relationship of mitral annulus velocities measured by TDI and STI have been compared and are related but not equivalent. 28 Septal and lateral mitral annulus TDI velocities of 8.3 (3) cmÁsec -1 and 11.0 (4.9) cmÁsec -1 , respectively, values in the normal range for the age group of that study, were found to correspond with STI velocities of 5.2 (1.8) cmÁsec -1 and 5.5 (2.1) cmÁsec -1 , respectively, which are similar to our results. The correlation of TDI and STI velocities was poor, (r = 0.4 and 0.3) for the septal wall and lateral walls, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…27 The relationship of mitral annulus velocities measured by TDI and STI have been compared and are related but not equivalent. 28 Septal and lateral mitral annulus TDI velocities of 8.3 (3) cmÁsec -1 and 11.0 (4.9) cmÁsec -1 , respectively, values in the normal range for the age group of that study, were found to correspond with STI velocities of 5.2 (1.8) cmÁsec -1 and 5.5 (2.1) cmÁsec -1 , respectively, which are similar to our results. The correlation of TDI and STI velocities was poor, (r = 0.4 and 0.3) for the septal wall and lateral walls, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…). Instead of just tracking and calculating the velocity of a region of interest in any direction, which the speckle tracking technique does by default, this method prevents misinterpretation of mitral annular motion caused by translational cardiac motion as described before . Reported global velocities were defined as the average from the 6 standard LV walls.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of just tracking and calculating the velocity of a region of interest in any direction, which the speckle tracking technique does by default, this method prevents misinterpretation of mitral annular motion caused by translational cardiac motion as described before. 16,20 Reported global velocities were defined as the average from the 6 standard LV walls. Data were exported to a spreadsheet program (Excel, Microsoft Corporation, Redmond, WA, USA) and mitral annular velocity was calculated by dividing the difference in length by the difference in time (Fig.…”
Section: Speckle Tracking Analysismentioning
confidence: 99%
“…In contrast, Kort et al. observed a poor agreement between the measurements from the two methods with no derivable uniform numeric correction 32 . Therefore, further studies are still needed to validate E/E′ values derived from STE with traditional E/E′ ratio and with filling pressures obtained by invasive measurement.…”
Section: Discussionmentioning
confidence: 96%
“…7 In contrast, Kort et al observed a poor agreement between the measurements from the two methods with no derivable uniform numeric correction. 32 Therefore, further studies are still needed to validate E/E values derived from STE with traditional E/E ratio and with filling pressures obtained by invasive measurement. It is also important to note that E/E ratios derived from various vendors' STE software may yield different cutoff values and that warrant further validation.…”
Section: Discussionmentioning
confidence: 99%